Features of understanding ethnic problems in German classical philosophy - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article provides a historical and philosophical overview of the development of ethnic issues in German classical philosophy. It analyses the writings of German philosophers (I. Kant, G. W. F. Hegel, and J. G. Fichte), whose works directly or indirectly address the ethnic issues. It is emphasised that a particular difficulty in reconstructing the philosophical legacy of the Enlightenment is presented by the semantically heterogeneous categorical apparatus, within which the concepts of «nation», «race», «ethnicity», and «people» often acted as identical and interchangeable categories.
Keywords: ethnos; spirit of the people; people; nation; race; language; I. Kant; J. G. Fichte; G. W. F. Hegel; primordialism; colonial discourse